Dual-frequency microstrip patch antennas and their application for IMT-2000 mobile handsets - Wang, Yajun. (2008)
Following the second generation (2G, 1996-2000), such as GSM/PCS-1900, US TDMA IS-136, PHS, and cdmaOne/IS-95, the International Telecommunication Union (ITU) has been in the process of developing family-standard for the third generation (3G) mobile cellular system, also known as IMT-2000, which will provide all-in-one services for voice, data, multimedia and Internet. Antennas are the essential element in mobile and cellular phones. This being the case, the portable antenna technology has grown side by side with mobile and cellular technologies.